Changing the Indian economy : renewal, reform and revival - Prasad, Rama; Rowley, Chris; Banerjee, Anurag Narayan (Elsevier Asian studies series., 2018)
Changing the Indian Economy: Renewal, Reform and Revival explores the fact that post-Modi India is witnessing unprecedented socioeconomic change, truly labeled as Modi's Mantra and his attempts to morph the Indian economic landscape. India is using an intelligent economic process for its renewal and growth, however, in a recent study by Nomura, 2016, The Japanese Financial Services firm, it is reported that there is downside risk to India's baseline forecast of 7.8 per cent GDP growth in 2016. Although the report suggests that there was a mid-cycle consolidation in mid-2014, the recovery seems to be losing momentum. This book offers a novel, but inclusive outlook to the entire post-Modi economic overhaul.